50 YEARS WITHOUT CHE: HASTA SIEMPRE, COMANDANTE! THE VISION OF LATIN AMERICA AND THE CONCEPT OF REVOLUTION OF GUEVARA - PROBLEMS AND NOTES - Menon, Gustavo (Universidade de São Paulo - Programa de Pós-graduação em Integração da América Latina, 2018)
After 50 years of his death, the ideas of Che Guevara continue to be object of discussions, reformulations and criticisms. The following study intends to discuss the vision of Latin America and the concept of revolution in the work of Ernesto Che Guevara. For this, in the light of his texts on the guerrilla war and the analysis of the Cuban Revolution of 1959, the article establishes the ideological dimensions of Guevarismo and its project to think the revolution in Latin America. In order to point out the peculiarities of Che's thought in the face of the other socialist currents of his time, in terms of revolutionary tactics and strategies, the present study points to the conceptual advances of his contributions. At the same time, without losing sight of the misunderstandings and limits of its formulations, the article aims to explain a Marxist critique of the errors of Foquism and the perception of Che Guevara on the material conditions of Latin American countries the 1960s.